Genetic diversity and clustering of pineapple (Annas comosus (L.) Merr.) genotypes using random amplified polymorphic DNA (RAPD) - Valencia, Lolita DC.; Castro, Sheryl D. (2011)
Genetic variation among 14 pineapple genotypes was assessed through molecular characterization using Random Amplified Polymorphic DNA (RAPD). RAPD was utilized to measure the genetic diversity and relationship among the different genotypes. The Doyle and Doyle extraction method was done in the DNA extraction of the 14 pineapple genotypes. Two Operon primers (OPY-15 and OPAV-06) were used in the PCR-based RAPD analysis of the different genotypes. Of the two primers used, OPY-15 (5'AGTCGCCCTT3') yielded consistent DNA polymorphic amplification in repeated trials and generated 11 banding patterns ranging from 0.40 -3.00bp. Using primer OPAV-06 (5'CCCGAGATCC3'), banding patterns formed were not clearly identified. Cluster analysis was done by similarity matrix within the NTSys program using unweighted pair-group method with arithmetic averages (UPGMA) to determine values of genetic distance. A dendrogram O ne 14 genotypes separated the pineapple cultivars and hybrids from the wild relatives. Based on the dendrogram at 0.76 similarity coefficient, the 14 genotypes were divided into four clusters: Cluster 1, Ananas bracteatus, Cluster - Smooth Cayenne', 'MD2'. Aklan' and 'MG3'; Cluster 3, 'Red Spanish', ‘Clone 74’, 'NP2' and 'Queen': and Cluster 4, 92-1 (hybrid), 'DM Gold', 92-2 (hybrid), ‘Sweet 16' and Calauan (ornamental-like). At 0.51 coefficient similarity, 3 clusters were generated: Cluster 1, Ananas bracteatus, Cluster 2, ‘Smooth Cayenne', 'MD2', 'Aklan', 'MG3', 'Red Spanish', 'Clone 74', ‘NP2’ and ‘Queen’; and Cluster 3.92-1 (hybrid), 'DM Gold'. 92-2 (hybrid), ‘Sweet 16’ and Calauan (ornamental-like). The RAPD of the 14 pineapple genotypes studied could be an ideal tool for detection of variation and relationship among genotypes and hence, can be useful in the assessment of genetic diversity and cluster analysis of pineapple germplasm accessions and varieties.
Keywords: Pineapple; genetic diversity; DNA analysis; Cluster analysis